Maternal Instincts in Bertolt Brecht’ s “Mother Courage and Her Children” (Journal of the College of Basic Education, 2023)
The research is concerned with the significance of the maternal instincts in Brecht’s Mother Courage and her Children.The portrait of a female in any society being a mother, a sister, a daughter, or a worker.The image of a woman in general and as a mother in particular as a great influence in life. The mother devotes her life for the demands of her children. Brecht deals with the mother as a business woman and how does she lose her children because of her greed and business.He tries to make his dramatic work as an instrument of a new idea for change